The Use of Indocyanine Green (ICG) and Near-Infrared (NIR) Fluorescence-Guided Imaging in Gastric Cancer Surgery: A Narrative Review - Belia, Francesco; Biondi, Alberto; Agnes, Annamaria; Santocchi, Pietro; Laurino, Antonio; Lorenzon, Laura; Pezzuto, Roberto; Tirelli, Flavio; Ferri, Lorenzo; D’Ugo, Domenico; Persiani, Roberto (Frontiers in Surgery, 2022)
Near-infrared fluorescence imaging with indocyanine green is an emerging technology gaining clinical relevance in the field of oncosurgery. In recent decades, it has also been applied in gastric cancer surgery, spreading among surgeons thanks to the diffusion of minimally invasive approaches and the related development of new optic tools. Its most relevant uses in gastric cancer surgery are sentinel node navigation surgery, lymph node mapping during lymphadenectomy, assessment of vascular anatomy, and assessment of anastomotic perfusion. There is still debate regarding the most effective application, but with relatively no collateral effects and without compromising the operative time, indocyanine green fluorescence imaging carved out a role for itself in gastric resections. This review aims to summarize the current indications and evidence for the use of this tool, including the relevant practical details such as dosages and times of administration.